Physics Conceptual Understanding of Tadris IPA Biology Students: Insights for Effective Conceptual Teaching Strategies - Prahastiwi, Rima Buana; Sholehah, Najah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to describe the level and characteristics of physics conceptual understanding among prospective science teachers in the Tadris IPA Biology program. The research employed a quantitative descriptive design using a survey method. Participants were 42 first-semester students enrolled in the Basic Physics course. Data were collected through a reasoning-based multiple-choice test consisting of ten valid items with a reliability coefficient of α = 0.623. The tested topics included quantities and measurements, linear and circular motion, temperature and heat, and optics. Descriptive statistical analysis and documentation of students’ written reasoning were used to identify conceptual difficulties and misconceptions. The results showed that students’ overall conceptual understanding was in the moderate category (3.95). The most frequent misconceptions occurred in the concepts of significant figures, acceleration in circular motion, heat transfer, and lens power in optics. These misconceptions were influenced by students’ weak conceptual understanding, reliance on rote memorization and intuitive reasoning, insufficient interactive and repetitive instruction, and the influence of prior learning or everyday experiences. These findings suggest that the learning process in the Tadris IPA Biology program should place greater emphasis on conceptual reinforcement, reasoning-based learning, and multi-representational approaches to improve students’ understanding of physics concepts.